KONTROL SOSIAL PELAKU KRIMINALITAS (STUDI TENTANG PENCURIAN KAMPUNG NELAYAN SRI MERANTI KECAMATAN RUMBAI KOTA PEKANBARU) - Usman, Fahruly Adha; Jalil, Ashaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research was conducted in the Sri Meranti Nelayan Village, Pekanbaru City with the aim of finding out the causes of theft or thieves Knowing the attitude of Social Control towards the environment in the village. The method used is a qualitative method. Data collection uses observation and in-depth interviews (In-depth Interview), and is equipped with documentation. The results of this study concluded that there were various factors caused by individual factors, economic factors, educational factors and parental factors. In addition, the factors that cause promiscuity and the environment are the lack of parental control and community attention to the environment., offices, or other public places. The rampant theft that has occurred has caused unrest for the community Keywords: Factors of Theft Against Actors and Social Control in Sri Meranti Fisherman's Village